SISTEM INFORMASI PADA AIESEC LAMPUNG BERBASIS WEB - Neni Purwati; Inas Yuni Tsamarah (Jurnal Teknoinfo, 2022)
AIESEC is an international organization for youth to develop their leadership potential. AIESEC is the largest student-driven organization in the world. An organization that focuses on developing youth leadership and serving as ambassadors abroad to carry out social projects. AIESEC also focuses on leadership development, leadership experience, and participation in the Global Learning Environment. This research produces an interface to facilitate AIESEC Lampung projects. This system was a facility for organizations to replace systems that used manual recording and  resulting in a lack of time efficiency. This system integrates data ranging from report data and transactions that had been stored in the database. The new system was designed using the RAD (Rapid Application Development) method. It was a linear sequential software development process that emphasized the development cycle in a short time iteratively (repetitively) in developing a system. A working model of the system was constructed in the early stages of development in defining the user requirements. With an integrated web-based computerized system, problems in transaction services at AIESEC Lampung can be solved easily. Reports and all transactions was displayed in the system. This research produced an Information System at AIESEC Lampung to carry out projects, namely the registration process and the host family program.Keyword: Information Systems, AIESEC, RUP, Web.